Aufruf! // An die Urnen: Wählt Schnitz und drunder!
politischer Rahmen;politisches System;Staat;Staatsform;Föderalismus;Bezirk politischer Rahmen;Wahlen und Abstimmungen;Wahl;Wahlorganisation;Wahlkampf politischer Rahmen;politisches System;Staat;Staatsform